Multinational cost-effectiveness analysis of pembrolizumab combined with chemotherapy as first-line treatment for advanced biliary tract cancer - Xie, Yuxuan; Liu, Quanyi; Xiao, Shanrui; Li, Xia; Qiu, Lin; Gu, Yun (Frontiers in Public Health, 2025)
BackgroundImmunotherapy is a promising treatment for advanced biliary tract cancer. However, the cost-effectiveness of pembrolizumab combined with gemcitabine and cisplatin remains unclear across different healthcare systems. This study evaluates its international cost-effectiveness in four countries.MethodsA partitioned survival analysis model was developed using data from the KEYNOTE-966 trial to compare costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratio (ICER) of pembrolizumab plus gemcitabine and cisplatin versus gemcitabine and cisplatin alone, from the healthcare system perspective of China, Japan, the United States, and Switzerland. Sensitivity and scenario analyses were used to identify key factors influencing the ICER.ResultsThe base-case analysis showed that pembrolizumab plus gemcitabine and cisplatin provided additional quality-adjusted life year gains of 0.14 in China, Japan, and the United States, and 0.15 in Switzerland. The incremental cost-effectiveness ratios in all four countries exceeded their respective willingness-to-pay thresholds, indicating limited cost-effectiveness. Sensitivity analysis identified drug price and utility value of progression-free survival as key factors. In the United States, Japan, and Switzerland, an 80–95% reduction in pembrolizumab’s price was necessary for cost-effectiveness, while in China, a reduction greater than 95% was required.ConclusionDespite clinical benefits, pembrolizumab combined with chemotherapy for advanced biliary tract cancer is not cost-effective at current prices and willingness-to-pay thresholds. Adjusting drug pricing and healthcare policies is crucial for enhancing the global economic viability of this treatment strategy.